2014
DOI: 10.1007/s12039-013-0559-7
|View full text |Cite
|
Sign up to set email alerts
|

Effective synthesis route for red-brown pigments based on Ce – Pr – Fe – O and their potential application for near infrared reflective surface coating

Abstract: New cerium-based ceramic pigments, displaying Ce 2 Pr 0.2 Fe x O 4.3+y stoichiometry, were obtained at low temperature using a sol-gel method. The powder precursor dissolved in 80% ethylene glycol was precipitated using ammonia and the obtained gel calcined at 800 • C for 2 h to yield homogeneous and crystalline particles with a diameter of around 150 nm. The oxide was composed of cerium in its +4 oxidation state and Pr in its +3 oxidation state. The oxides with varying Fe content had an intense red-brown colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Brightness weakness (L * values), even in the case of glycine fuel samples, is due to the residual carbons, to the formation of acceptable greyish brown pigment, onestep without calcination. 40,42,43 As expected, the fuel mixture is intermediate and does not reach the brightness of the sample obtained by glycine and urea fuels. Contrary to popular belief, the simultaneous presence of glycine and urea did not have a synergistic effect and reduced the yellowness-redness color.…”
Section: 5supporting
confidence: 51%
See 2 more Smart Citations
“…Brightness weakness (L * values), even in the case of glycine fuel samples, is due to the residual carbons, to the formation of acceptable greyish brown pigment, onestep without calcination. 40,42,43 As expected, the fuel mixture is intermediate and does not reach the brightness of the sample obtained by glycine and urea fuels. Contrary to popular belief, the simultaneous presence of glycine and urea did not have a synergistic effect and reduced the yellowness-redness color.…”
Section: 5supporting
confidence: 51%
“…For example, in the case of glycine–urea fuel mixture, the conditions are better than urea, but it does not reach glycine, and as a result, no synergistic effect was observed from the fuel mixture. In another sense and compared to glycine fuel, the mixture of fuels reduced the quality of the hue and chroma, which can be due to the heterogeneity created by the addition of two fuels with different properties 40,41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In particular, development of novel red pigments has been required and several studies have been reported. [18][19][20][21][22][23][24][25][26][27] Among them, it has been reported that Ca 1Àx La x TaO 2Àx N 1+x and Ce 2 S 3 showed bright red colour. 18,19 But, unfortunately, harmful NO x and SO x are generated when these nitride and sulphide pigments are incinerated.…”
Section: Introductionmentioning
confidence: 99%
“…Among the lanthanides, praseodymium exhibits excellent optical characteristics manifested in several interesting praseodymium complexes of high luminescence efficiency or for applications as color pigments and in near-infrared reflective coatings . Moreover, praseodymium forms oxides with variable valence states (3+ and 4+) such as Pr 2 O 3 , PrO 2 , and Pr 6 O 11 that are stable under ambient conditions, making them promising functional oxide materials.…”
Section: Introductionmentioning
confidence: 99%